Community social support as a protective factor against suicide: A gender-specific ecological study of 75 regions of 23 European countries. (November 2017) - Zadravec Šedivy, Nuša; Podlogar, Tina; Kerr, David C.R.; De Leo, Diego
Abstract: By studying differences in suicide rates among different geographical regions one may identify factors connected to suicidal behaviour on a regional level. Many studies have focused on risk factors, whereas less is known about protective factors, such as social support. Using suicide rates and data from the European Social Survey (ESS) we explore the association between regional level social support indicator and suicide rates in 23 European countries in 2012. Linear multiple regression analyses using region as the unit of analysis revealed inverse relationships between mean respondent valuing of social support and suicide rates for both genders, with some indication of a stronger relationship among men. Social support may have a protective effect against suicide on a regional level. Thus, increasing social support could be an effective focus of preventive activities, resulting in lowering suicide rates, with greater expected results among men. Highlights: Social support may have a protective effect against suicide. Increasing social support in communities could be a valuable part of prevention. The most benefits of higher social support could be noted among men. Social support enhancement can be most beneficial in high suicide rates regions.